BIG DATA ANALYTICS IN PHARMACOVIGILANCE - A GLOBAL TREND - RANI AITHA, SWETHA; MARPAKA, SRAVANI; T, CHAKRADHAR; E, BHUVANESHWARI; RANI KASUKURTHI, SWARUPA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Big data analysis has enhanced its demand nowadays in various sectors of health-care including pharmacovigilance. The exact definition of big data is not known to many people though it is routinely used by them. Big data refer to immense and voluminous computerized medical information which are obtained from electronic health records, administrative data, registries related to disease, drug monitoring, etc. This data are usually collected from doctors and pharmacists in a health-care facility. Analysis of big data in pharmacovigilance is useful for early raising of safety alerts, line listing them for signal detection of drugs and vaccines, and also for their validation. The present paper is intended to discuss big data analytics in pharmacovigilance focusing on global prospect and domestic country-India.